Protocol for a multicentre randomised controlled trial examining the effects of temporarily pausing Bruton tyrosine kinase inhibitor therapy to coincide with SARS-CoV-2 vaccination and its impact on immune responses in patients with chronic lymphocytic leukaemia - Abhishek Abhishek; Jonathan A Cook; Helen M Parry; Anne Francis; Lelia Duley; Vicki S Barber; Paul Moss; Nicholas Peckham (BMJ Open)
Introduction People who are immunocompromised have a poor biological response to vaccinations. This study aims to determine in patients with chronic lymphocytic leukaemia (CLL) if a 3-week pause in Bruton tyrosine kinase inhibitor therapy (BTKi) starting 1 week before delivery of SARS-CoV-2 vaccine booster, improves vaccine immune response when compared with continuation of BTKi.Methods and analysis An open-label, randomised controlled superiority trial will be conducted in haematology clinics in approximately 10 UK National Health Service (NHS) hospitals. The sample size is 120, randomised 1:1 to intervention and usual care arms. The primary outcome is anti-spike-receptor binding domain (RBD) antibody level at 3 weeks post-SARS-CoV-2 booster vaccination. Secondary outcomes are RBD antibody levels at 12 weeks postbooster vaccination, participant global assessments of disease activity, blood films, full blood count and lactate dehydrogenase levels, impact on quality of life, self-reported adherence with request to temporarily pause or continue BTKi, T cell response against spike protein and relative neutralising antibody titre against SARS-CoV-2 viral variants. Additionally, there will be an investigation of any effects in those given influenza vaccination contemporaneously versus COVID-19 alone.The primary analysis will be performed on the as randomised groups (‘intention to treat’). The difference between the study arms in anti-spike-RBD antibody level will be estimated using a mixed effects regression model, allowing for repeated measures clustered within participants. The model will be adjusted for randomisation factor (first line or subsequent line of therapy), and prior infection status obtained from prerandomisation antinucleocapsid antibodies as fixed effects.Ethics and dissemination This study has been approved by Leeds East Research Ethics Committee and Health Research Authority (REC Reference:22/YH/0226, IRAS ID: 319057). Dissemination will be via peer-review publications, newsletters and conferences. Results will be communicated to participants, the CLL patient and clinical communities and health policy-makers.Trial registration number ISRCTN14197181.